Prevalence of constipation among peritoneal dialysis patients in Saudi Arabia: A single-center study - Ahmad Raed Tarakji; Hussam Zaid Alorabi; Yazeed Abdullah Alhusainy; Nasser Yousef Alhowaish; Abdullah Abdulaziz Alsebti; Hamad Sulaiman Aljutaili (Wolters Kluwer Medknow Publications, 2021)
Objectives: Constipation among peritoneal dialysis (PD) patients can lead to serious complications and impair the quality of life. The aim of this study was to determine the prevalence of constipation and its associated factors among PD patients in our center. Methods: A quantitative, cross-sectional study was conducted on PD patients at King Khaled University Hospital in Riyadh, Saudi Arabia, from November 2016 to January 2017. Results: A total of 36 PD patients were included; the male to female ratio was 1. Based on a self-reporting questionnaire, 15 PD patients (41.7%) reported suffering from constipation. However, the prevalence was the same using at least one of Rome III criteria (41.7%) and much lower using Bristol stool form Scale (11%). No significant difference was detected between PD patients with and without constipation in terms of dietary fiber intake, use of calcium and iron supplements, water intake, presence of diabetes and hypertension, or demographic profiles. Conclusion: The high prevalence of constipation among PD patients seen in our population is comparable to those seen in other studies.